AI and Auditing: Enhancing Audit Efficiency and Effectiveness with Artificial Intelligence - Lidiana, Lidiana (Penelitian dan Pengembangan Ilmu, 2024)
The use of automation and artificial intelligence (AI) in audit practice is increasingly becoming a major focus, with significant impact on the profession. This research depicts the current landscape of the use of AI in auditing, highlighting aspects such as automation and empowerment of the workforce in auditing, impact of AI on improving audit quality criteria, key factors in adopting AI-based audit techniques, impact of AI technology on audit evidence , and auditors' perceptions of AI in improving audit quality. The results and discussion show that while there are great benefits from integrating automation and AI in auditing, including improved audit quality, enhanced efficiency, and the ability to perform continuous audits, there are also challenges that need to be overcome, such as high customization costs for specific audit processes industry. The use of AI in auditing requires adaptation from auditors to changes in competencies and workflows to effectively utilize this technology. However, with proper understanding and careful handling of these challenges, AI has great potential to improve overall audit practices.